Pengaruh Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa SMP - Tri Muhammad Rahmatullah; Sripatmi Sripatmi; Eka Kurniawan; Laila Hayati (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine whether there is an influence of learning motivation and learning style on the mathematics learning outcomes of eighth grade students of SMP Negeri 5 Palibelo in the Academic Year 2021/2022. The population in this study were all seventh grade students in the odd semester of the 2021/2022 academic year at Nageri 5 Palibelo Junior High School, Bima Regency, which consisted of two classes of 35 students. Determination of the sample is done by using the remote sampling technique. The data analysis technique used in this study is SPSS using descriptive statistical data analysis and inferential statistics. This researcher uses instruments in the form of questionnaires and test questions. The results showed that there was a significant effect of learning motivation on students' mathematics learning outcomes with a correlation coefficient of 0.932. In the regression analysis, a constant value of 0.749 was obtained. from other factors, as well as the contribution given by 86.9%.